A Review on the Status of Rubber Plantations in Cambodia - Im Hol; Sor Ratha; Serey Mardy (MultiTech Publisher, 2024)
The rubber tree (natural rubber) is a tropical crop around the world. In Cambodia, rubber is one of the most popular agro-industrial crops introduced since the 1910s. This study review article aims to demonstrate the methods for planting and harvesting techniques in rubber plantations. Cultivation is the most important factor in the rubber sector, and planting is done during June and July. Moreover, selecting varieties of clonal rubber is the best way to improve high production, high initial vigor, tolerance to climate change, pests, wind damage, and diseases, and to be a good secondary characteristic. In addition, harvesting techniques are vital elements in the status of rubber plantations. So, improving the methods of cultivation and the techniques of harvesting is very important in order to get a high amount of rubber production.